Basic genetic and biological markers of psoriasis - Olga O. Melnichenko; Elena V. Denisova; Olga V. Zhukova; Nikolay N. Potekaev (ZAO "Consilium Medicum", 2021)
Background. Psoriasis is a chronic inflammatory autoimmune disease characterized by an excessively aberrant hyperproliferation of keratinocytes. The pathogenesis of psoriasis is complex, and the exact mechanism, despite numerous studies, is still unclear. Complex genetic relationships play an important role in the pathogenesis of this skin disease. A large number of genes that are also associated with other diseases are involved in the development of psoriasis. The variety of comorbidities in patients with psoriasis often present challenges to the treatment for dermatosis. Understanding the role of certain genes in the pathogenesis of psoriasis will contribute the development of more effective targeted therapy aimed at blocking the corresponding inflammatory signaling pathways and molecules. Aim. To analyze and systematize the basic genetic and biological markers of psoriasis. Materials and methods. The study included research articles on the genetic analysis of psoriasis. The ResNet, PubMed and eLibrary databases were used. Results and discussion. Basic genetic and biological markers were identified by analysis of literature sources devoted to psoriasis. Attention is paid to the role and effects of single nucleotide polymorphisms, which make it possible to establish a clear association of a number of genes involved in the development of psoriasis. Genes with altered expression in the psoriatic process were considered separately. Conclusion. The identified biomarkers can be used in targeted biological therapy of psoriasis using biological modulators that block signaling.